The Multivariate Regression in Mathcad - A. Abdurazakov; N.A. Makhmudova; N.T. Mirzamakhmudova (Genius Journals, 2022)
This article discusses the construction of linear multifactorial models that determine for specific examples using the MathCAD software product, which makes it possible to make a decision
Keywords: linearity; multivariate model; dependency vector